Prevention of COVID-19 infection in swimming competitions - Takahashi, M.; Matsunami, M.; Sakai, T. (Japanese Journal of Sciences in Swimming and Water Exercise, 2021)
The purpose of this study was to examine of countermeasures to infection in swimming competitions under COVID-19 pandemic. In swimming competitions, the same criteria as for other sporting events cannot be used, because participants use the spectators' seats. In a swimming competition, crowded and/or close-contact situations are not formed, since each swimmer uses each lane in the race. However, swimmers in a competition may be crowded in the warm-up pool and locker room. Therefore, it is necessary to consider the control of the number of participants in the swimming competition in the order of the locker room and the warm-up pool. The results of this study show that the number of swimmers using the locker room at the same time is an important factor.